Stakeholder engagement in economic evaluation: Protocol for using the nominal group technique to elicit patient, healthcare provider, and health system stakeholder input in the development of an early economic evaluation model of chimeric antigen receptor T-cell therapy - Dean A Fergusson; Manoj M Lalu; Ian D Graham; Justin Presseau; Kednapa Thavorn; Kelvin KW Chan; Daniel A Ollendorf; Natasha Kekre; Terry Hawrysh; Harold Atkins; Doug Coyle; Mackenzie Wilson (BMJ Open)
Introduction Chimeric antigen receptor T-cell (CAR-T) therapy is a class of immunotherapy. An economic evaluation conducted at an early stage of development of CAR-T therapy for treatment of adult relapsed or refractory acute lymphoblastic leukaemia could provide insight into factors contributing to the cost of treatment, the potential clinical benefits, and what the health system can afford. Traditionally, stakeholders are engaged in certain parts of health technology assessment processes, such as in the identification and selection of technologies, formulation of recommendations, and implementation of recommendations; however, little is known about processes for stakeholder engagement during the conduct of the assessment. This is especially the case for economic evaluations. Stakeholders, such as clinicians, policy-makers, patients, and their support networks, have insight into factors that can enhance the validity of an economic evaluation model. This research outlines a specific methodology for stakeholder engagement and represents an avenue to enhance health economic evaluations and support the use of these models to inform decision making for resource allocation. This protocol may inform a tailored framework for stakeholder engagement processes in future economic evaluation model development.Methods and analysis We will involve clinicians, healthcare researchers, payers, and policy-makers, as well as patients and their support networks in the conduct and verification of an early economic evaluation of a novel health technology to incorporate stakeholder-generated knowledge. Three stakeholder-specific focus groups will be conducted using an online adaptation of the nominal group technique to elicit considerations from each. This study will use CAR-T therapy for adults with relapsed or refractory B-cell acute lymphoblastic leukaemia as a basis for investigating broader stakeholder engagement processes.Ethics and dissemination This study received ethics approval from the Ottawa Hospital Research Institute Research Ethics Board (REB 20200320-01HT) and the results will be shared via conference presentations, peer-reviewed publications, and ongoing stakeholder engagement.